Character education and personal social guidance counseling and its effects on personal social competences - Diana Septi Purnama (JOURNAL OF EDUCATION, 2014)
This study was aimed at finding a concept model of appropriate guidance for developing adolescent personal social competences. More specifically, the study attempted to find the correlation between personal social guidance counseling and character education in schools and the private social competence of students. The subjects were 1,500 high school students in Yogyakarta who have received character education programs in their school. The primary data were collected by questionnaires. The secondary data were collected by observation and documentation. Data were analysed qualitatively for cross-check purposes and quantitatively for statistical hypothesis testing. Findings showed that there was evidence for the fact that personal social guidance counseling helps develop personal social competence of teenagers.